The Routledge companion to severe, profound and multiple learning difficulties - Lacey, Penny; Ashdown, Rob; Jones, Phyllis; Lawson, Hazel; Pipe, Michele (London Routledge, 2015)
"With contributions from leading experts and academics in the field, this timely companion to the education of children severe, profound and multiple learning difficulties will be an essential resource for students and practitioners alike. It contains a myriad of topics and themes, from learning contexts and understanding difficulties through to curriculum development and issues in teaching and learning. The overall context is one of services and families working together to ensure the best education and care possible.The contributors cover topics related to the full range of Early Years, Primary, Secondary and Further Education, and combine the very latest research with practical application for anyone who wishes to reflect on and improve their practice. Each chapter includes boxed case study examples gathered from practitioners in the field, is written specifically to be rigorous yet accessible to busy practitioners, and boasts multiple contributions to ensure breadth and balance"--Provided by publisher.
"The Routledge Companion to Severe, Profound and Multiple Learning Difficulties is a timely and rich resource with contributions from leading experts and academics in the field. It is an essential resource for students and practitioners alike. The book contains a myriad of topics and themes, from learning contexts and understanding difficulties through to curriculum development and issues in teaching and learning. The overall context is one of services and families working together to ensure the best education and care possible. The contributors cover topics related to the full range of Early Years, Primary, Secondary and Further Education, and combine the very latest research with practical application for anyone who wishes to reflect on and improve their practice. Each chapter includes boxed case examples gathered from practitioners in the field, is written specifically to be rigorous yet accessible to busy practitioners, and boasts multiple contributions to ensure breadth and balance. The book has been split into six main sections: Provision in the UK for Learners with SLD/ PMLD Involving Stakeholders Priorities for Meeting the Personal and Social Needs of Learners Developing the Curriculum Strategies for Supporting Teaching and Learning Moving Forwards This text is a crucial read, not just for teachers but also to support staff, speech and language therapists, physiotherapists, psychologists, nurses, social workers and other specialists interested in improving the quality of education and support for children and young people with severe, profound and multiple learning difficulties and their families"--Provided by publisher.
Introduction / Penny Lacey, Rob Ashdown, Phyllis Jones, Hazel Lawson and Michele Pipe -- Learners with SLD and PMLD : provision, policy and practice / Dawn Male -- Changing special educational needs and disability legislation and policy : implications for learners with SLD/PMLD / Christopher Robertson -- An historical reflection on education for learners with SLD/PMLD, 1800-1970 / David Stewart -- Priorities, products and process : developments in providing a curriculum for learners with SLD and PMLD / David Stewart -- Further education : personalised destinations and outcomes for students with SLD/PMLD / Caroline Allen, Kathrine Everett, Janet Sherborne, James Stonard, Joanne Yarlett -- Building secure foundations in the early years / Michele Pipe, Fiona Smith and Lesley Mycroft -- Joint working for learners with SLD/ PMLD / Penny Lacey with Julian Brown, Fiona Holmes, Helen Burnford, Kate Jones and Rosie Jones -- Working with families : partnerships in practice / Barry Carpenter & Hollie Rawson -- Provision for children with severe and profound learning difficulties from ethnic minority families / Sana Rizvi and Peter Limbrick -- Participation, citizenship and voice / Sana Rizvi and Peter Limbrick -- Participation, citizenship and voice / Hazel Lawson and Ann Fergusson with Miranda Brookes, Trudy Duffield and Anthony Skipworth -- Training and developing the inclusive teacher for learners with SLD & PMLD / Melanie Peter -- Teachers talking about their work with learners with SLD & PMLD / Michael Riley and Phyllis Jones -- Ups and downs : how learners with SLD/ PMLD view their school experience / Elizabeth Henderson, Julia Barnes and Nicola Grove -- Learners with severe and profound and multiple learning difficulties and sensory impairments / Liz Hodges and Mike McLinden -- Care as an educational concept / Peter Imray and Lana Bond -- Sex and relationship education / David Stewart, Angela Mallett and Tom Hall -- Physical contact experiences within the curriculum / Julia Barnes and Dave Hewett -- Hidden behind a label, an uneasy relationship between mental health and special needs / Ann Fergusson, Marie Howley, Rachel Allan and Richard Rose -- Spirituality and severe learning difficulties / Jean Ware and Erica Brown -- Death, bereavement and loss / Erica Brown -- Curriculum models, issues and tensions / Hazel Lawson and Richard Byers with Matthew Rayner, Richard Aird and Laura Pease -- Recognising progress : assessing outcomes for young people with SLD and PMLD / Richard Byers and Ann Fergusson -- Communication / Juliet Goldbart and Jean Ware -- Intensive interaction : fundamental and early communication abilities / Dave Hewett, Graham Firth, Lana Bond and Riana Jackson -- Inclusive talking : language learning / Carolyn Anderson and Penny Lacey with Suzanne Kavanagh and Kalvinder Rai -- The teaching of reading to pupils with SLD / Sarah Mosely -- Literature and stories in the lives of pupils with SLD/PMLD / Nicola Grove, Jane Harwood, Elizabeth Henderson, Keith Park and Rosemary Bird -- Using number in everyday life / Jill Porter -- Physical education for all learners / Steve Cullingford Agnew with Nigel Carter, Anne Craddock, Chris Rollings, Barbara Dowson and Hannah Brighton -- Technology supporting learning / Chris Abbott and Ann Middleton -- Playing to learn or learning to play? : ideas on ensuring that the opportunity to play is continually accessible for learners with SLD/PMLD / Peter Imray and Robert Orr -- Supporting playfulness in learners with SLD/PMLD : going beyond the ordinary / Debby Watson and Margaret Corke -- The learning environment / Penny Lacey with Yvonne McCall, Jodie Dunn and Lisa Watson -- Engaging with research / Jill Porter -- The way ahead / Rob Ashdown.
Includes bibliographical references and index.
Keywords: Learning disabled children -- Education -- Great Britain; Learning disabled -- Education -- Great Britain; Learning disabled -- Services for -- Great Britain; Learning disabilities -- Great Britain; Special education -- Great Britain